Nitrogen substitutional defects in silicon. A quantum mechanical investigation of the structural, electronic and vibrational properties - Platonenko, Alexander; Gentile, Francesco Silvio; Pascale, Fabien; Ferrari, Anna Maria; D’Amore, Maddalena; Doves, Roberto (Royal Society of Chemistry, 2019)
The vibrational infrared (IR) and Raman spectra of seven substitutional defects in bulk silicon are computed, by using the quantum mechanical CRYSTAL code, the supercell scheme, an all electron Gaussian type basis set and the B3LYP functional. The relative stability of various spin states has been evaluated, the geometry optimized, the electronic structure analyzed. The IR and Raman intensities have been evaluated analitically. In all cases the IR spectrum is dominated by a single N peak (or by two or three peaks with very close wavenumbers), whose intensity is at least 20 times larger than the one of any other peak. These peaks fall in the 645–712 cm−1 interval, and a shift of few cm−1 is observed from case to case. The Raman spectrum of all defects is dominated by an extremely intense peak at about 530 cm−1, resulting from the (weak) perturbation of the peak of pristine silicon.
RD and FSG acknowledges the CINECA award (HP10CTG8YY) under the ISCRA initiative, for the availability of high performance computing resources and support.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics